Forcing of cool and warm subsurface water events in Bahía Salinas, Costa Rica - Alfaro Martínez, Eric J. (2021)
Introduction: Bahía Salinas, on the north Pacific coast of Costa Rica, is a seasonal upwelling area. Sea temperature in Bahía Salinas could be modulated by synoptic and other large-scale systems. This region belongs to the Central American Dry Corridor (CADC), a sub-region in the isthmus that is relatively drier than the rest of the territory, which extends along the Pacific littoral from western Guatemala through northern Costa Rica. Objective: To study the warm and cold events that could be inferred by studying the sea subsurface temperature in Bahía Salinas, and also analyzing the large-scale conditions and synoptic systems of the historical sources when they occurred in order to identify the atmospheric mechanisms that favored their appearance. Methods: A Sea Subsurface Temperature Index was calculated using hourly data from seven stations located at three different points in Bahía Salinas. Records range from June 19, 2003 to December 5, 2017. Additionally, six meteorological stations, with hourly wind records, were used to create two wind indices. The Sea Subsurface Temperature Index was used to identify the warmest and coldest events in the bay. Wind indices and monthly meteorological bulletins were used to analyze the large-scale conditions and synoptic systems in which cold and warm events occurred in Bahía Salinas. Results: Mean sea temperature in Bahía Salinas is 25.2°C. Colder temperatures were observed in FebruaryMarch, below 21°C. There were two maxima in May-June and August-October with temperatures above 27°C. In four of the five cold events studied, Northeasterly wind anomalies were observed in the Costa Rican North Pacific, associated with trade wind reinforcements; meanwhile westerly anomalies were observed in all the warm events, associated with weaker trade wind conditions. Conclusions: The main seasonal climate driver in Bahía Salinas is the North Atlantic Subtropical High because its latitudinal migration is associated with the strength of the trade winds over Central America. Seasonal upwelling is modulated also by two synoptic scale climate features, the boreal winter arrival of cold front outbreaks and the winter maximum of the easterly Caribbean Low-Level Jet. El Niño-Southern Oscillation is also an important modulator of the sea temperature variability, since warm and cool events are related with positive and negative sea temperature anomalies.